CollectiveCity: the right to the city: 50 years later - Garcia Ruiz, M.; Henriques, C.; Chaves, H. (2018)
The Third International Conference of Young Urban Researchers (TICYUrb) started the different sessions with the track CollectiveCity, the right to the city: 50 years later, commemorating the publication of "The Right to the City", one of the best well-known works of Henri Lefebvre. This track was divided in four sessions: Reflections on the Right to the City, Urban Resistance, Tourism and Urban Conflict and Housing Policies. Papers in this book are some of the works presented in the different sessions mentioned. These, and other works, responded to a challenge that we had launched to young urban researchers following Lefebvre’s lections today, especially on the emergent field of the Urban Studies. Lefebvre criticized an urban reality in which exchange value overlapped with use value, "right to urban life, transformed and renewed: "a right that concretizes collective needs, both for access to certain resources and for spatial appropriation or creative action on it. Several authors have made important contributions to the current reflection on the right to the city, among them: David Harvey, who understands the city as a work and, consequently, as an extension of the human being; and Neil Brenner, who has been reflecting on the process of planetary urbanization. In this sense, given the current importance of cities in a context of increasing urbanization, the different authors address the question on what is the current situation of the right to the city?